PEMIKIRAN KOMPUTASIONAL GURU DALAM PENINGKATAN KETERAMPILAN PERENCANAAN PEMBELAJARAN MATEMATIKA - Firdaus, Ahmad Qolfathiriyus; Agustin, Ririn Dwi (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2026)
This study examines how secondary school mathematics teachers use computational thinking (CT) in lesson planning to improve students' mathematical skills in a dimension that has been largely overlooked in the CT literature. Although CT is generally promoted as a technology-based and student-centred competency, this qualitative study shows that teachers naturally integrate core CT practices, namely decomposition, pattern recognition, abstraction, and algorithmic thinking, as implicit cognitive tools in designing learning, even in schools with limited resources and without formal CT policies. Based on an analysis of lesson plans and semi-structured interviews with 25 teachers from various school contexts, the findings indicate that CT is not applied as an external addition, but rather as a hidden heuristic for organising conceptual understanding and procedural skills. Teachers routinely break down complex mathematical procedures into structured steps, recognise patterns of student errors, devise general strategies that apply across topics, and systematically organise exercises, all without using digital devices or explicit CT terminology. This finding challenges the dominant narrative originating from developed countries, which tends to equate CT with programming or high technology, and instead positions CT as an inherent part of flexible and cross-disciplinary professional pedagogical reasoning. This research proposes a shift in the theoretical framework: CT is not only a learning objective for students, but also a cognitive resource for teachers. The implications are important for teacher education, curriculum design, and fair and contextual CT policies, while paving the way for scalable CT integration in various global contexts.